A novel five‐lipoxygenase activity protein inhibitor labeled with carbon‐14 and deuterium. (20th July 2015) - Latli, Bachir; Hrapchak, Matt; Gao, Joe J.; Busacca, Carl A.; Senanayake, Chris H.
<x xml:space="preserve">Abstract</x> 2‐[4‐(3‐(1R)‐1‐[4‐(2‐Aminopyrimidin‐5‐yl)phenyl]‐1‐cyclopropylethyl‐1, 2, 4‐oxadiazol‐5‐yl)‐1H‐pyrazol‐1‐yl]‐N, N‐dimethylacetamide (1), is a novel and selective five‐lipoxygenase activity protein (FLAP) inhibitor with excellent pharmacokinetics properties. The availability of a key chiral intermediate allowed the synthesis of [14C]‐(1) in six radiochemical steps and in 47% overall radiochemical yield with a specific activity of 51 mCi/mmol using carbon‐14 zinc cyanide. 2‐Chloro‐N, N‐dimethyl‐2H6‐acetamide was prepared and condensed with a penultimate intermediate to give [2H6]‐(1) in very high yield and in more than 99% isotopic enrichment.